Wildlife-habitat relationships : - Morrison, Michael L. (Island Press, 2006)
Wildlife-Habitat Relationships goes beyond introductory wildlife biology texts to provide wildlife professionals and students with an understanding of the importance of habitat relationships in studying and managing wildlife. The book offers a unique synthesis and critical evaluation of data, methods, and studies, along with specific guidance on how to conduct rigorous studies. Now in its third edition, Wildlife-Habitat Relationships combines basic field zoology and natural history, evolutionary biology, ecological theory, and quantitative tools in explaining ecological processes and their influence on wildlife and habitats. Also included is a glossary of terms that every wildlife professional should know.